PENETAPAN HARGA PADA TRANSAKSI JUAL BELI ANTARA PENGRAJIN JAMPEL DENGAN PENGEPUL (Ahkam: Jurnal Hukum Islam, 2022)
In this article, we try to analyze the concept of price fixing in Islam which actually has the aim of giving birth to benefits in every transaction. Pricing is also useful to cut imbalances that occur in the market. In Islam itself, the concept of price fixing has a principle, namely by considering the needs of the transaction actors so that there are no disputes. However, if there is an action approaching or even an act of zhulm (a disgraceful act) even an act that causes injustice, the government also has a hand in helping to combat the imbalance by fixing prices and looking at the factors that cause imbalances, then setting prices. so that balance is reborn. Based on the pre-study that has been found by researchers, there is a partnership transaction between jampel craftsmen and collectors, precisely in Tulungagung district which according to researchers, regarding the price fixing that has been set by collectors is the price with the minimum profit earned by jampel craftsmen. The purpose of this research is to find out whether the transaction process carried out by jampel craftsmen and collectors is in accordance with the concept of pricing in Islam. The research method used is conducting a case study by observing the transaction process carried out by jampel craftsmen with collectors and understanding the pricing factors set by collectors to jampel craftsmen and analyzing using theories of pricing concepts in Islam. The results of this study are an imbalance that occurs related to the prices that have been determined by the collectors, hereby, based on the concept of pricing in Islam, the collectors do not realize the benefits in the transaction process they do together with jampel craftsmen.